2021
DOI: 10.1097/pgp.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Lymphovascular Space Invasion Is an Adverse Prognostic Factor in High-Risk Endometrial Cancer

Abstract: Approximately 15% of patients with endometrial cancer present with high-risk disease (HREC). Moreover, assessing the extent of lymphovascular space invasion (LVSI) may provide prognostic insight among patients with HREC. The aim of this study was to determine whether the extent of LVSI can serve as a prognostic factor in HREC. All cases of ESMO-ESGO-ESTRO 2016 classified HREC in the Danish Gynecological Cancer Database (DGCD) diagnosed from 2005 to 2012 were reviewed for the presence and extent of LVSI (catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…LVSI is a known risk factor for lymph node metastasis, recurrence and shorter survival in EC [8,[36][37][38][39]. Studies have now reported on the clinical relevance of assessing the extent of LVSI, independent of other clinicopathological features [16,39,40]. The prognostic role of substantial LVSI has previously been explored in the context of the molecular subgroups in intermediate (−high) risk EC patients [3,40], where substantial LVSI was an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LVSI is a known risk factor for lymph node metastasis, recurrence and shorter survival in EC [8,[36][37][38][39]. Studies have now reported on the clinical relevance of assessing the extent of LVSI, independent of other clinicopathological features [16,39,40]. The prognostic role of substantial LVSI has previously been explored in the context of the molecular subgroups in intermediate (−high) risk EC patients [3,40], where substantial LVSI was an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…There were 713 patients with high-grade EC registered in the DGDC, of which 460 had haematoxylin and eosin-stained slides available for pathology review regarding assessment and quantification of LVSI, by four pathologists, as described in detail by Peters et al [16](Supplementary methods), and selection of tumour tissue for molecular profiling. Formalin-fixed paraffin-embedded tumour tissue was collected from 426 EC.…”
Section: Patient Selectionmentioning
confidence: 99%
“…An extensive body of literature supports these findings. Randomized trials, prospective cohort studies, large database series, and single-institution reports consistently demonstrate that LVSI is an independent and strong prognostic factor for the recurrence of endometrial carcinoma [ 66 67 68 69 ]. A retrospective registry study of more than 1,500 patients from Sweden with Stage I–III identified LVSI as the strongest independent risk factor for lymph node metastases and decreased survival, even in the absence of lymph node metastases in patients with endometrioid adenocarcinomas [ 67 ].…”
Section: Figo Staging Of Endometrial Cancermentioning
confidence: 99%
“…In contrast to substantial LVSI, minimal or focal LVSI has limited impact on prognosis. [12][13][14] Alongside these characteristics, L1 cell adhesion molecule (L1CAM) is another significant indicator of high-risk disease. 15,16 Expression of L1CAM is most frequent in p53-abnormal (p53-abn) tumours but is also predictive of worse outcome among tumours with no specific molecular profile (NSMP).…”
Section: Diagnosis Pathology and Molecular Biologymentioning
confidence: 99%